An application data security with lempel-ziv welch and blowfish - Rahim, Robbi; Adyaraka, Danadyaksa; Sallu, Sulfikar; Sarimanah, Eri; Hidayat, Arif; Sewang, Anwar; Hartinah, Sitti (International Journal of Engineering and Technology, 2018)
This research uses Blowfish algorithm which is part of Algorithm Encryption in cryptography. The Blowfish algorithm is part of symmetric cryptography, which is the key used for encryption equal to the key used for decryption. Besides the security of the file, the size problem of a file is also a calculation. Large files can be compressed by performing the LZW compression process is one of the compression algorithms that use dictionary. The merger between the cryptographic algorithm and the compression algorithm ensures that files cannot be viewed by unauthorized users, ensuring files can be stored in low-capacity media all of which lead to faster delivery.Â Â